Dynamic compressive properties of new metallic hollow sphere concrete composites. (27th February 2023) - Dai, Meiling; Liang, Junping; Wang, Xirui; Lu, Zhongyu
Graphical abstract: Highlights: Dynamic properties of new metallic hollow sphere concrete composites were studied. Addition of MHSs into concrete increased the strain rate sensitivity significantly. MHSCCs showed excellent energy absorption capacity under impact loads. The content of MHS influenced the dynamic responses of MHSCCs noticeably. Adding polypropylene fibre improved the compressive strength and toughness of MHSCCs. Abstract: The dynamic properties of new metallic hollow sphere concrete composites were investigated experimentally. Metallic hollow spheres (MHSs) at volume fractions of 10 %, 20 % and 30 % were embedded into a concrete matrix to form metallic hollow sphere concrete composites (MHSCCs) under normal temperature conditions. Dynamic compression tests using a split Hopkinson pressure bar were conducted at strain rates in the 15 s −1 ∼ 80 s −1 range on the specimens after 28 d of curing. The conditions of the concrete matrix, with and without polypropylene fibres, were tested for comparison. The failure modes, stress–strain curves, dynamic strengths, and energy absorption capacities were analysed. The results indicated that the damage degree increased with increasing MHS content and strain rate. The composites were more sensitive than plain concrete to the strain rate. Adding a certain amount of MHSs into the concrete matrix improved the dynamic compressive strength and the overall energy absorption by up to 25.4 % and 317 %, respectively, at a strain rate of approximately 70 s −1 . The addition of polypropylene fibre further improved the dynamic properties of the composites due to the bridging effect of fibres; however, it had a negative influence on the dynamic increase factor.